If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3c = 2c + 4 Reorder the terms: 4 + 3c = 4 + 2c Add '-4' to each side of the equation. 4 + -4 + 3c = 4 + -4 + 2c Combine like terms: 4 + -4 = 0 0 + 3c = 4 + -4 + 2c 3c = 4 + -4 + 2c Combine like terms: 4 + -4 = 0 3c = 0 + 2c 3c = 2c Solving 3c = 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 3c + -2c = 2c + -2c Combine like terms: 3c + -2c = 1c 1c = 2c + -2c Combine like terms: 2c + -2c = 0 1c = 0 Divide each side by '1'. c = 0 Simplifying c = 0
| -2+8=-8 | | (3+5)7= | | v+12=5v | | 10-6(11m+3)=-2m-8(1-7m) | | 5(5)+9y=7 | | -2n+6=7 | | 9K-K=40 | | 8-4N= | | 2(b+4)=40 | | 2(x+5)-3(x-8)=0 | | -2p+4=p-8 | | 34-x=14x | | a^4+a^2b^2+b^4=8 | | 3w=63 | | 2x+5=3x-10 | | 27-6a=7+4d | | 24=-1.3 | | 24=-1.5 | | 3w-3x-y+7w+17x-4y= | | 2x^3+14x^2=-24x | | 6(a-1)=4(a+2) | | 3(n+3)=9+4n | | 12x-2y+15w+3y-5w+2x= | | 1.5n=-9 | | 7m+4n-4m+8n= | | 7w+10y+11x+3x-15y+4w= | | 4(v+9)+12=-(v-3) | | 4(v+9)+12=-(v-3) | | 4x^2-24x-30=0 | | 3x-2=-1 | | 3x-2=-1 | | 3x-2=-1 |